The antecedents and consequences of health information seeking and behavioral intention - K. Y. S. Putri; Abdullah, Zulhamri; Raza, Syed Hassan; Istiyanto, S. Bekti (Allied Business Academies, 2021)
The information and communication technologies, health information seeking, and citizens’ behavioral intention has been established as a promising area of attention. However, recent growth in digital health information surveillance has dynamics of information-seeking behavior entirely. The paper, therefore, aims to develop a digital literacy conceptual framework to understand the dynamics of Online Health Information Seeking (hereafter OHIS) and Behavioral Intention. Drawing an analogy from past health behavior and information-seeking theories, this conceptual framework provides guidelines for future quantitative studies. The study employed the literature review method and extracted the past empirical and review studies from the most reliable databases using the search words. In total, 10 years dataset of the published work has been used as a sample published from 2010 to 2020. The study analyzed the published work and advanced the body of knowledge by proposing the understudied tradeoff between information quality, perceived value, perceived personal health value, and trust in OHIS intention. Thereby, the theoretical foundation offered in this study supports the further investigations taping antecedents and consequences of OHIS intention in Asia. The research also identified the Hospital’s corporate image as a moderating variable that possibly intensifies the influence of the antecedents as mentioned above on OHIS intention. The empirical validation of this model could assist policymakers and Malaysian and Indonesian citizens to understand the health information seeking and behavioral patterns of people in a digital age.